DESIRE AND PLEASURE IN THE BRANDED REALITY SHOW AS A DISCURSIVE PSYCHOANALYSIS - Bambang Sukma Wijaya (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The study of branded reality show is still very limited, especially in the perspective of discursive psychoanalysis. In fact, the phenomenon of reality show is currently growing in the television industry, so brands are inspired to create similar programs. This paper aims to analyze the desire and pleasure of success are presented and disclosed by branded reality show ‘Diplomat Success Challenge’ on a national TV channel in Indonesia. Using discursive psychoanalysis method in the Lacanian perspective, author found that participants in the ‘Diplomat Success Challenge’ saw competitors (other participants) as ‘other’ in imaginary phase which is the object of desire in having the pleasure of success, while the audience used the praticipants as reflection of their desire and pleasure of success. There are two tendencies of the spectatorship style in responding to the discourse. In one hand the audiences tend to be more emphatic and figural, while on the other hand they tend to be more logic and systematic. In addition, the desire and pleasure of success in the ‘Diplomat Success Challenge’ becomes a powerful discourse that alienated negative issues related to the Diplomat as a tobacco product brand. Thus, the politics of reality through a discourse of success in the branded reality show has successfully infiltrated into the subconscious and control the public consciousness.